Historical Note: A letter from Cayetano Heredia ignored - Lastres, Juan B. (1952)
Every day, the national heuristic, scattered in archives, libraries and individuals, providing new light on the activities of our proto doctors. This we publish now and has the date 1840, when Heredia planned reorganization of medical studies indicates Heredia efforts to secure income to support the decadent School of Independence. Needed to shore up their "short rents" and poach others to give the range that would be, of higher education. College entries were considerably reduced by the little attention he had borrowed from the government, as he was careful to maintain public order, disrupted by various revolutions, and that income was not sufficient to meet the expenses of urgency. So suggest a package to the government, that the branch of Census and temporalities, whose products were intended for public instruction, a party to the College in order to cover part of the 3,300 pesos to be paid annually by the national treasure is taken. With a beneficial resolution to this effect could make some progress in improving the teaching of the various chairs and so do good work nationally, promoting "public health, national honor and decorum of the medical sciences."